1997
DOI: 10.1074/jbc.272.44.28001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of cDNAs Corresponding to an Additional Member of the Human Histone Deacetylase Gene Family

Abstract: Several human cDNAs encoding a histone deacetylase protein, HDAC3, have been isolated. Analysis of the predicted amino acid sequence of HDAC3 revealed an open reading frame of 428 amino acids with a predicted molecular mass of 49 kDa. The HDAC3 protein is 50% identical in DNA sequence and 53% identical in protein sequence compared with the previously cloned human HDAC1. Comparison of the HDAC3 sequence with human HDAC2 also yielded similar results, with 51% identity in DNA sequence and 52% identity in protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
306
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(318 citation statements)
references
References 32 publications
9
306
2
1
Order By: Relevance
“…Similar to HDACs 1 and 2, HDAC3 is also ubiquitously expressed. As expected by the sequence identity, early functional analysis of the HDAC3 protein revealed common features with HDACs 1 and 2, namely deacetylation of histone substrates, transcriptional repression when targeted to promoters, as well as physical association with the DNA-binding factor YY1 (Yang et al, 1997;Dangond et al, 1998;Emiliani et al, 1998). Together, these findings suggested that this ubiquitously expressed protein could be involved in the regulation of mammalian gene expression.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Similar to HDACs 1 and 2, HDAC3 is also ubiquitously expressed. As expected by the sequence identity, early functional analysis of the HDAC3 protein revealed common features with HDACs 1 and 2, namely deacetylation of histone substrates, transcriptional repression when targeted to promoters, as well as physical association with the DNA-binding factor YY1 (Yang et al, 1997;Dangond et al, 1998;Emiliani et al, 1998). Together, these findings suggested that this ubiquitously expressed protein could be involved in the regulation of mammalian gene expression.…”
Section: Introductionsupporting
confidence: 55%
“…Its open reading frame predicted a 428 aa protein, with an estimated molecular mass of 49 kDa. Human HDAC3 is 53% identical with human HDAC1 and 52% identical with human HDAC2 at the amino acid level (Yang et al, 1997;Dangond et al, 1998). This similarity led to the classification of the above three proteins into one family.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…E1A interacts with various chromatin modifying proteins, (reviewed by Mymryk and Smith, 1997), some of which display histone acetyltransferase (HAT) activity, such as the transcriptional coactivators CBP/p300 (Ogryzko et al, 1996) and TAF II -250 (Geisberg et al, 1995;Mizzen et al, 1996). Other E1A binding proteins are directly associated with histone deacetylase proteins (HDAc's), like the Rb family of transcriptional repressors (Luo et al, 1998;Brehm et al, 1998;Magnaghi et al, 1998;Ferreira et al, 1998) and the transcriptional regulators YY-1 (Lee et al, 1995;Lewis et al, 1995;Yang et al, 1997) and CtBP (Schaeper et al, 1995;Sundqvist et al, 1998).…”
Section: Introductionmentioning
confidence: 99%